Biogenic synthesis of Iron oxide nanoparticles via optimization of nitrate reductase Enzyme using statistical experimental design - zaki, sahar (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
Statistically designed experiments were proceeded to evaluate nutritional and environmental parameters that affect nitrate reductase enzyme (NR) activity in Achromobacter sp. KT735046. Plackett-Burman design was performed for screening and identifying efficiently the significance of 15 culture conditions influencing NR activity. FeCl3 ·6H2O, Na2MoO4 ·2H2O and CuSO4.5H2O were the most significant variables positively influencing, whereas pH was the most significant negative contributors. The optimal levels of significant factors were further predicted from five level factorial designs, Central Composite Design (CCD). The optimum parameter values were CuSO4.5H2O (60.375) mg/l, FeCl3·6H2O (240 mg /L), pH (6.135) and Na2MoO4·2H2O (150 mg /L). The biogenic Iron oxide nanoparticles "IONPs" were characterized; the dark brown IONPs exhibit maximum absorption from 400 to 464 nm, XRD reveals crystallite rhombohedral hematite, EDX confirms presence of 62% of iron, TEM illustrates formation of tiny IONPs, 1.4 and 2.8 nm in size, Î¾ potential and PDI recorded -42.9 mV and 0.268 respectively exhibiting high stability and monodispersed with no agglomeration by the help of biomolecules. This study conclude that Achromobacter sp. KT735046 consider being biofactory for synthesis nanoparticles by the help of NR enzyme and it may be the first time to optimize Achromobacter sp. KT735046 for IONPs biosynthesis using statistical designs.